2009
DOI: 10.1186/1757-1626-2-7400
|View full text |Cite
|
Sign up to set email alerts
|

Combined anomalous origin of a left inferior thyroid artery and a left vertebral artery: a case report

Abstract: An abnormal origin of a left inferior thyroid artery from the left vertebral artery that in turn originated from the aortic arch was observed on a 72-year-old Caucasian male cadaver during a dissection anatomy practice. We describe in detail the morphology of this extremely rare anatomical variation and refer to its clinical importance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 10 publications
2
4
0
Order By: Relevance
“…2). This corresponds to the reports of left VA origin as a branch from the root of left SCA close to the AA [10] or of left VA "in touch" with left SCA [11]. This form of very close origin of VA and SCA by one specific common widening of AA we consider as not prop- originating region, in terms of one common or two separate openings of related vessels or of blood flow patterns in this region.…”
Section: Discussionsupporting
confidence: 72%
“…2). This corresponds to the reports of left VA origin as a branch from the root of left SCA close to the AA [10] or of left VA "in touch" with left SCA [11]. This form of very close origin of VA and SCA by one specific common widening of AA we consider as not prop- originating region, in terms of one common or two separate openings of related vessels or of blood flow patterns in this region.…”
Section: Discussionsupporting
confidence: 72%
“…It was seen as a branch from root of left subclavian artery close to the arch of aorta by Konstantinos Natsis et al [24] and a similar variation was observed in the present study in one case (Figure 2). …”
Section: Variations In the Origin Of Vertebral Arteries 411 Left Vesupporting
confidence: 89%
“…The Inferior thyroid artery (ITA) is the chief artery which supplies the posterior and inferior parts of the thyroid gland and parathyroid glands [15]. The ITA is generally larger and the more important one from the point of view of occlusion to reduce the vascularity of goiters and a route for exposure of truncal ligation of this vessel has been worked out on the cadaver and practice [18]. CONCLUSION…”
Section: Institutionalmentioning
confidence: 99%